8th LICMAS 2024 Book of Abstracts - Conference Scientific Committee (AlQalam Journal of Medical and Applied Sciences, 2024)
This is a collection of abstracts that was submitted for the participation in the 8th Libyan International Conference on Medical, Applied, and Social Sciences 2024 held by the University of Tripoli Alahlia between the period of 27-29 June 2024